GSK-3β at the Intersection of Neuronal Plasticity and Neurodegeneration. (2nd May 2019) - Jaworski, Tomasz; Banach-Kasper, Ewa; Gralec, Katarzyna
Abstract : In neurons, Glycogen Synthase Kinase-3 β (GSK-3 β ) has been shown to regulate various critical processes underlying structural and functional synaptic plasticity. Mouse models with neuron-selective expression or deletion of GSK-3 β present behavioral and cognitive abnormalities, positioning this protein kinase as a key signaling molecule in normal brain functioning. Furthermore, mouse models with defective GSK-3 β activity display distinct structural and behavioral abnormalities, which model some aspects of different neurological and neuropsychiatric disorders. Equalizing GSK-3 β activity in these mouse models by genetic or pharmacological interventions is able to rescue some of these abnormalities. Thus, GSK-3 β is a relevant therapeutic target for the treatment of many brain disorders. Here, we provide an overview of how GSK-3 β is regulated in physiological synaptic plasticity and how aberrant GSK-3 β activity contributes to the development of dysfunctional synaptic plasticity in neuropsychiatric and neurodegenerative disorders.